Longitudinal Measurements and Beam Tuning in the J-PARC Linac MEBT1. (November 2019) - Otani, M.; Futatsukawa, K.; Miyao, T.; Liu, Y.; Hirano, K.; Kondo, Y.; Miura, A.; Oguri, H.
Abstract: The Japan Proton Accelerator Research Complex (J-PARC) linac is operated with design peak current of 50 mA from 2018. For operation with such a high beam current, it is important to understand transverse and longitudinal beam properties especially in low-velocity region. A medium energy beam transport (MEBT1) line between the 3-MeV radio-frequency quadrupole linac (RFQ) and the 50-MeV drift-tube linac (DTL) is a 3-m-long transport line to match the beam to the DTL and produces a macro pulse configuration for a 3-GeV rapid-cycling synchrotron (RCS). In this paper, recent measurements and beam tuning results in MEBT1 will be presented.